TOLERANCE OF THE TRANSMIGRATION COMMUNITY IN TABOLANG VILLAGE, TOPOYO DISTRICT, MAMUJU CENTRAL REGENCY - Sahril Nur (UNM Geographic Journal, 2022)
This study aims to determine the form of tolerance of the transmigration community, the supporting factors of tolerance and the inhibiting factors of tolerance, and efforts to maintain the tolerance of the transmigration community in Tabolang Village, Topoyo District, Central Mamuju Regency. The research method used is descriptive qualitative method and combined with quantitative research methods. Data collection techniques using observation, interviews, questionnaires, and documentation. which aims to reveal facts or occurrences of variable phenomena and circumstances that occurred during the research by presenting what actually happened and by adding the results of the questionnaire as supporting data from the results obtained through interviews if needed. The data analysis technique used interactive analysis and descriptive statistical analysis.The results of the study based on data analysis showed that the form of tolerance of the transmigration community was seen from sixteen indicators, this was generally carried out by the transmigration community in Tabolang Village, Topoyo District, Central Mamuju Regency. This is also in accordance with the percentage level of tolerance in the form of transmigration society obtained in the high category of 74 percent. The supporting factors for community tolerance, seen from the five indicators, tend to be carried out by the transmigration community in Tabolang Village, Topoyo District, Central Mamuju Regency as a form of supporting the creation of diverse community tolerance. In addition, the most influential and dominant factor carried out by the transmigration community is respecting the beliefs of others of 86. The inhibiting factor of community tolerance seen from the four indicators, this tends to be carried out by the transmigration community in Tabolang Village, Topoyo District, Central Mamuju Regency as a form of inhibiting the creation of community tolerance diverse. Of these four factors, the factors that most tend to hinder the tolerance of transmigration communities are poor education and love to live in hostility. However, these four factors are classified as high in inhibiting the tolerance of the transmigration community based on the results of the questionnaire data which obtained an average of above 70 percent. Efforts to build community tolerance seen from two indicators, are generally carried out by transmigration communities in Tabolang Village, Topoyo District, Central Mamuju Regency as an effort to maintain a form of tolerance for transmigration communities that exist in diverse communities. Of these two factors, all of them are high and the factor that most transmigration people tend to do in an effort to maintain community tolerance is that it requires social interaction through intensive conversation and association by 73 percent. This shows that the form of tolerance of the transmigration community is generally carried out by the community so that it needs to be maintained or developed for the better.